Design of an assembly concrete brick that facilitates the laying of bricks with the KUKA robot in the absence of an automated system in the construction of masonry walls - Victor, Bustios Calle Diego (2023)
Currently, the construction sector is the least automated in Peru and the world, because the activities in the work have processes that differ from each other. Likewise, the most predominant material in the walls is brick or cement block according to the 2017 National Census of Peru because they represent 4,298,274 homes, which represents 55.8% of the total private homes in Peru. This means that one of the most important construction activities in Peru is the manufacture of masonry walls. In addition, 80% of the total houses in Peru are informal according to CAPECO (2021), therefore, an automated system is needed to optimize cost and time in masonry work. In the present investigation, the focus is on designing an assemblable brick with less weight than the King Concrete brick and a resistance greater than 20 kg/cm2, which is the minimum indicated by the Peruvian masonry standard.